自然数的平方和公式

2025-02-28 20:47:13
推荐回答(3个)
回答1:

1^2+2^2+3^2+4^2+5^2………………+n^2=n(n+1)(2n+1)/6

数学归纳法可以证
也可以如下做 比较有技巧性
n^2=n(n+1)-n
1^2+2^2+3^2+......+n^2
=1*2-1+2*3-2+....+n(n+1)-n
=1*2+2*3+...+n(n+1)-(1+2+...+n)

由于n(n+1)=[n(n+1)(n+2)-(n-1)n(n+1)]/3
所以1*2+2*3+...+n(n+1)
=[1*2*3-0+2*3*4-1*2*3+....+n(n+1)(n+2)-(n-1)n(n+1)]/3
[前后消项]
=[n(n+1)(n+2)]/3

所以1^2+2^2+3^2+......+n^2
=[n(n+1)(n+2)]/3-[n(n+1)]/2
=n(n+1)[(n+2)/3-1/2]
=n(n+1)[(2n+1)/6]
=n(n+1)(2n+1)/6

回答2:

(a+b)^2=a^2+2*a*b+b^2
(a+b+c)^2=((a+b)^2+2*(a+b)*c+c^2)=a^2+2*a*b+2*a*c+2*b*c+c^2+b^2
........
........

回答3: